URGENSI REKONSTRUKSI SANKSI PIDANA TERHADAP KORPORASI DALAM SEKTOR PERTAMBANGAN MINERAL DAN BATUBARA DI KOTA SAMARINDA - V Zahry, Sarkowi (Gapenas Publisher, 2025)
This research aims to analyze the effectiveness of the enforcement of criminal sanctions against corporations in the coal mining sector in Samarinda City. Mining activities managed by corporations, whether private or regional, have been proven to cause serious environmental and social impacts, ranging from ecosystem destruction to an increased risk to community safety. However, the provisions in Law Number 4 of 2009 have not provided a clear operational basis regarding corporate criminal liability. This study uses a juridical-empirical approach by combining normative studies and field data through interviews and literature review. The results show that the enforcement of criminal law against corporations in Samarinda generally only focuses on administrative sanctions, thus failing to create a deterrent effect. The main obstacles include weak regulations, weak institutional coordination, economic-political considerations, and limited capacity of law enforcement officials. Based on these findings, this study recommends the need for a reconstruction of criminal sanctions that are stricter, more comprehensive, and oriented towards ecological justice to strengthen corporate accountability and provide optimal protection for society and the environment.